Inducible knockout of Mef2a, ‐c, and ‐d from nestin‐expressing stem/progenitor cells and their progeny unexpectedly uncouples neurogenesis and dendritogenesis in vivo. Issue 12 (18th August 2015) - Latchney, Sarah E.; Jiang, Yindi; Petrik, David P.; Eisch, Amelia J.; Hsieh, Jenny
ABSTRACT: Myocyte enhancer factor (Mef)‐2 transcription factors are implicated in activity‐dependent neuronal processes during development, but the role of MEF2 in neural stem/progenitor cells (NSPCs) in the adult brain is unknown. We used a transgenic mouse in which Mef2a, ‐c, and ‐d were inducibly deleted in adult nestin‐expressing NSPCs and their progeny. Recombined cells in the hippocampal granule cell layer were visualized and quantified by yellow fluorescent protein (YFP) expression. In control mice, postmitotic neurons expressed Mef2a, ‐c, and ‐d, whereas type 1 stem cells and proliferating progenitors did not Based on this expression, we hypothesized that Mef2a, ‐c, and ‐d deletion in adult nestin‐expressing NSPCs and their progeny would result in fewer mature neurons. Control mice revealed an increase in YFP + neurons and dendrite formation over time. Contrary to our hypothesis, inducible Mef2 KO mice also displayed an increase in YFP + neurons over time—but with significantly stunted dendrites—suggesting an uncoupling of neuron survival and dendritogenesis. We also found non‐cell‐autonomous effects after Mef2a, ‐c, and ‐d deletion. These in vivo findings indicate a surprising functional role for Mef2a, ‐c, and ‐d in cell‐ and non‐cell‐autonomous control of adult hippocampal neurogenesis that is distinct from its role during development.—Latchney, S. E., Jiang, Y., Petrik, D. P., Eisch, A. J., Hsieh, J. Inducible knockout of Mef2a, ‐c, and ‐d from nestin‐expressing stem/progenitor cells and their progeny unexpectedly uncouples neurogenesis and dendritogenesis in vivo. FASEB J. 29, 5059–5071 (2015). www.fasebj.org